Valuation Effects of Cancelled Debt Offerings - Jensen, Marlin R. H.; Pugh, William N. (Journal of Financial and Quantitative Analysis, 1991)
We examine the price behavior of the firm's common stock associated with cancelled straight debt offerings. Excluding utilities, we find negative excess returns associated with offering and cancellation announcements. Further, the stronger withdrawal reactions we find, when the funds were to be used for capital expenditures, may signal a decline in profitable investment opportunities. These results are consistent with Miller and Rock's (1985) hypothesis.